Comparative Analysis of Streptococcus pneumoniae Type I Restriction-Modification Loci: Variation in hsdS Gene Target Recognition Domains - Melissa B. Oliver; W. Edward Swords (Pathogens, 2020)
Streptococcus pneumoniae (pneumococcus) is a respiratory commensal pathogen that causes a range of infections, particularly in young children and the elderly. Pneumococci undergo spontaneous phase variation in colony opacity phenotype, in which DNA rearrangements within the Type I restriction-modification (R-M) system specificity gene hsdS can potentially generate up to six different hsdS alleles with differential DNA methylation activity, resulting in changes in gene expression. To gain a broader perspective of this system, we performed bioinformatic analyses of Type I R-M loci from 18 published pneumococcal genomes, and one R-M locus sequenced for this study, to compare genetic content, organization, and homology. All 19 loci encoded the genes hsdR, hsdM, hsdS, and at least one hsdS pseudogene, but differed in gene order, gene orientation, and hsdS target recognition domain (TRD) content. We determined the coding sequences of 87 hsdS TRDs and excluded seven from further analysis due to the presence of premature stop codons. Comparative analyses revealed that the TRD 1.1, 1.2, and 2.1 protein sequences had single amino acid substitutions, and TRD 2.2 and 2.3 each had seven differences. The results of this study indicate that variability exists among the gene content and arrangements within Type I R-M loci may provide an additional level of divergence between pneumococcal strains, such that phase variation-mediated control of virulence factors may vary significantly between individual strains. These findings are consistent with presently available transcript profile data.